Bacterial and Fungal Numbers in Ruminal and Cecal Contents of the Blue Duiker (Cephalophus monticola) - Dehority, Burk A. (1991)
Total and cellulolytic bacterial and fungal numbers were determined in ruminal and cecal contents of 20 blue duikers (Cephalophus monticola). The animals were equally divided by sex and fed two diets, either high roughage or high concentrate. The mean concentration for total bacterial numbers in the rumen was 26.0 × 10(8)/g of contents, with values ranging from 2 × 10(8)/g to 93 × 10(8)/g. Cellulolytic numbers averaged 6.0 × 10(8)/g with a range of 1.5 × 10(8)/g to 24.0 × 10(8)/g. No differences related to sex or diet were found. In contrast, total bacterial numbers in the cecum differed between diets (P < 0.02), i.e., 1,046 × 10(6) bacteria per g for animals fed the high-forage diet compared with 166 × 10(6)/g for those fed the high-concentrate diet. Cellulolytic bacterial counts in the cecal contents averaged 3.1 and 7.0% of the total counts for the high-forage and high-concentrate diets, respectively. Low concentrations of fungi were found in both ruminal and cecal contents of some, but not all, animals. Unexpectedly, concentrations of bacteria and fungi in the rumen and cecum were highly correlated with their total numbers (concentration multiplied by total weight of contents).